Protein-protein interaction site mapping using NMR-detected mutational scanning. - Baminger, B; Ludwiczek, M; Kontaxis, G; Knapp, S; Konrat, R (2007)
We demonstrate a novel NMR method for the mapping of protein-protein interaction sites. In our approach protein-protein binding sites are mapped by competition binding experiments using indirect NMR reporter technology and Ala positional scanning. The methodology provides high sensitivity, ease of implementation and high-throughput capabilities. The feasibility of the technique is demonstrated with an application to the beta-Catenin/Tcf4 complex.